Identification of surrogate endpoints in patients with locoregionally advanced nasopharyngeal carcinoma receiving neoadjuvant chemotherapy plus concurrent chemoradiotherapy versus concurrent chemoradiotherapy alone. Issue 1 (December 2015) - Chen, Yu-Pei; Zhang, Wen-Na; Tang, Ling-Long; Mao, Yan-Ping; Liu, Xu; Chen, Lei; Zhou, Guan-Qun; Mai, Hai-Qiang; Shao, Jian-Yong; Jia, Wei-Hua; Kang, Tie-Bang; Zeng, Mu-Sheng; et al.
Abstract Background In the era of intensity-modulated radiotherapy (IMRT), the efficacy of additional neoadjuvant chemotherapy (NACT) to concurrent chemoradiotherapy (CCRT) in locoregionally advanced nasopharyngeal carcinoma (NPC) is currently being investigated in ongoing trials. Overall survival (OS) is the gold standard endpoint in NPC trials. We performed this analysis to identify surrogate endpoints for OS, which could shorten follow-up duration and speed up assessment of treatment effects. Methods We retrospectively analysed 208 matched-pair patients with locoregionally advanced NPC receiving NACT+CCRT or CCRT. Progression-free survival (PFS), failure-free survival (FFS), distant failure-free survival (D-FFS) and locoregional failure-free survival (LR-FFS) at 2 and 3 years were assessed as surrogates for 5-year OS according to Prentice's criteria. The strength of the associations were assessed using Spearman's rank correlation coefficient. Results No significant differences were observed between treatment arms for any surrogate endpoint at 2 years, which rejected Prentice's second criterion. In contrast, 3-year LR-FFS, PFS, FFS and D-FFS were consistent with all four of Prentice's criteria; the rank correlation coefficient (0.730) between 3-year PFS and 5-year OS was highest. Conclusions 3-year PFS, FFS and D-FFS could be valid surrogate endpoints for 5-year OS; 3-year PFS may be the most accurate.